THE ROLE OF SHORT-CHAIN FATTY ACIDS IN IMMUNE REGULATION AND INTESTINAL HOMEOSTASIS IN INFLAMMATORY BOWEL DISEASE - Marta Czarnowska,; Radosław Sciepuro,; Nina Czarnowska,; Katarzyna Malinowska,; Dawid Cyls,; Elhatra Settaf-Cherif,; Joanna Barwacz,; Magdalena Adamik,; Dagmara Gładysz,; Agnieszka Zaleszczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is characterized by chronic relapsing intestinal inflammation driven by dysregulated immune responses and impaired epithelial barrier function. Increasing evidence highlights short-chain fatty acids (SCFAs)—particularly acetate, propionate, and butyrate—produced by gut microbiota as key mediators linking microbial composition to immune regulation and maintenance of intestinal homeostasis.Methodology: This review was conducted through an extensive analysis of clinical, experimental, and translational studies indexed in PubMed, Google Scholar, and the Cochrane Library, focusing on gut microbiota composition, SCFA metabolism, epithelial barrier integrity, immune mechanisms, and SCFA-targeted therapeutic strategies in IBD.Results: Patients with IBD consistently show reduced abundance of SCFA-producing bacteria, especially butyrate-generating taxa such as Faecalibacterium and Roseburia, accompanied by decreased fecal SCFA levels and impaired epithelial SCFA utilization. SCFAs exert potent anti-inflammatory effects via histone deacetylase inhibition and activation of SCFA-responsive G protein-coupled receptors, promoting regulatory immune phenotypes and suppressing pro-inflammatory signaling. Concurrently, they enhance intestinal barrier function by stimulating mucus production, reinforcing tight junctions, and supporting epithelial metabolic activity. Dietary fiber enrichment, prebiotics, probiotics, and microbiota-directed therapies demonstrate potential to restore SCFA availability and improve inflammatory and clinical outcomes, although responses remain heterogeneous.Conclusions: SCFAs represent a crucial interface between gut microbiota, immune regulation, and epithelial barrier integrity, positioning SCFA-related mechanisms as promising therapeutic targets in IBD. Despite encouraging evidence, further well-designed, mechanistic, and personalized studies are needed to clarify causality, optimize SCFA-based interventions, and translate findings into effective clinical strategies.